Los espacios lúdicos y el desarrollo de la creatividad en los niños y niñas de educación inicial y parvularia de la escuela fiscal mixta Víctor Gerardo Aguilar Arévalo del recinto Shumiral perteneciente al cantón Camilo Ponce Enríquez. - Aucay Barzallo, Mónica Lucia (2014)
This research is important because it seeks to highlight the importance of play activities as a stimulus in the process of development of the child and the child, just as the need to recreate in the world with a new language through early experiences loaded imagination, spontaneous, natural and effective way to acquire learning more pleasantly.